Biogeography of arbuscular mycorrhizal fungal spore traits along an aridity gradient, and responses to experimental rainfall manipulation. (August 2020) - Deveautour, Coline; Chieppa, Jeff; Nielsen, Uffe N.; Boer, Matthias M.; Mitchell, Christopher; Horn, Sebastian; Power, Sally A.; Guillen, Alberto; Bennett, Alison E.; Powell, Jeff R.
Abstract: Spore size, colour and melanin content are hypothesised to be functional in relation to environmental stress. Here, we studied AM fungal spores in arid environments of Australia and in an experimental platform simulating altered rainfall. We used microscopy and image analysis to measure spore colour and size, and a quantitative colorimetric assay to estimate melanin content in spores. In arid sites, melanin content tended to increase with increasing aridity. We observed a large range of spore colours at all sites but found a higher proportion of both dark and light spores, and fewer intermediate colours, in drier sites. Spore abundance and size varied among sites, but neither were related to aridity. In the experimental platform established in a grassland, we found no evidence that altered rainfall influenced spore traits. This study identifies traits associated with environmental stress to inform future work into AM fungal life history and assembly processes. Highlights: We studied AM fungal spore traits associated with environmental stress. Melanin content tended to be higher in drier sites. We found more dark and light spores, and few intermediate colours, in drier sites. Average spore density varied among arid sites, but not in relation to aridity. We found no evidence that changes in rainfall for 22 months influenced spore traits.